The Effect Of Financial Technology And Financial Capability On Financial Satisfaction With The Mediation Of Financial Behavior - Iswinarti Margiana; Lutfi Lutfi (UNIVED Press, 2025)
This study aims to analyze the effect of Financial Technology and Financial Capability on Financial Satisfaction with Financial Behavior as a mediating variable. The research was conducted on household financial managers in Pasuruan City using a quantitative survey approach. The sampling technique combined purposive and snowball sampling, and the collected data were analyzed using Partial Least Squares (PLS-SEM). The results indicate that Financial Technology, Financial Capability, and Financial Behavior each have a positive and significant effect on Financial Satisfaction. Furthermore, Financial Behavior was found to partially mediate the relationship between Financial Technology and Financial Satisfaction, but it did not significantly mediate the relationship between Financial Capability and Financial Satisfaction. These findings highlight that while financial technology adoption and financial capability directly enhance satisfaction, financial behavior plays a crucial role in strengthening the positive effect of technology adoption. The study contributes both theoretically and practically by providing empirical evidence on the role of financial behavior in the digital era and offering insights for policymakers and financial institutions to design more effective financial literacy and inclusion strategies.